Brentuximab vedotin with AVD shows safety, in the absence of strong CYP3A4 inhibitors, in newly diagnosed HIV-associated Hodgkin lymphoma. (13th March 2018) - Rubinstein, Paul G.; Moore, Page C.; Rudek, Michelle A.; Henry, David H.; Ramos, Juan C.; Ratner, Lee; Reid, Erin; Sharon, Elad; Noy, Ariela
Abstract : Objective: Brentuximab vedotin is a Food and Drug Administration approved anti-CD30 antibody drug conjugate potently active in Hodgkin lymphoma. Trials of brentuximab vedotin with doxorubicin, vinblastine, and dacarbazine (AVD-BV) excluded patients with HIV. We studied the safety of AVD-BV in newly diagnosed HIV-associated classical Hodgkin lymphoma . Design and methods: Patients diagnosed with stage II–IV HIV-associated classical Hodgkin lymphoma received AVD-BV on days 1 and 15 every 28 days for six cycles. Anti-HIV medications with strong CYP3A4 inhibition were excluded. This phase 1 trial followed a 3+3 dose de-escalation design started with brentuximab vedotin at 1.2 mg/kg with standard dosing of AVD. Dose-limiting toxicities were defined in cycle one. Results: Seven patients were enrolled with six being evaluable: five of six stage III/IV, three with an international prognostic score at least 4. With no dose-limiting toxicities identified, all six were treated at the 1.2 mg/kg dose. Only five grade (G) three nonhematological adverse events were noted in three patients: pulmonary infection, diarrhea, and peripheral neuropathy. No G4/5 adverse events occurred. PET/computer tomography was negative in five of six after cycle 2 and six of six post therapy. Progression-free survival was 100% at 25 months with all patients in remission. One patient was deemed ineligible for taking ritonavir, a strong CYP3A4 inhibitor, but developed G3/4 adverse events including febrile neutropenia, and pancreatitis and though consented was excluded from all evaluation. Conclusion: AVD-BV was well tolerated at recommended phase 2 dose of 1.2 mg/kg. Concurrent strong CYP3A4 inhibitors should be avoided. A phase 2 study of AVD-BV is currently enrolling (NCT01771107). Abstract : Supplemental Digital Content is available in the text